2019
DOI: 10.22271/ortho.2019.v5.i2a.02
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of stabilization of shaft clavicle fractures using intramedullary nailing vs plating

Abstract: Background: Clavicle fractures account for approximately 2-4% of all adult fractures and about half of all fractures in the shoulder girdle. Conservative management poften leads to cosmetic deformities, complications such as axillary pressure sores, upper extremity edema and venous congestion, brachial plexus palsy, worsening of deformity and increased risk for non-union. There are two commonly performed surgical techniques used to repair displaced midshaft clavicle fractures, open reduction and plate fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The findings of the study showed a promising role of TENS as compared to plating in management of midshaft clavicle fractures. Sharma et al (2019) [15] in a comparative study that included 50 midshaft clavicle fracture cases used plating and TENS for surgical treatment in 25 cases each. Mean age of patients in plating and TENS groups was 35.84 and 36.02 years respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study showed a promising role of TENS as compared to plating in management of midshaft clavicle fractures. Sharma et al (2019) [15] in a comparative study that included 50 midshaft clavicle fracture cases used plating and TENS for surgical treatment in 25 cases each. Mean age of patients in plating and TENS groups was 35.84 and 36.02 years respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-bent anatomic plates proposed in past decades have been recommended for the treatment of various types of fractures, especially for particular types of complex fractures [6] . Clinical results show that pre-bent plates contribute to the functional recovery of patients and enhance the success rate of the fracture treatment [7] [8] .…”
Section: Introductionmentioning
confidence: 99%